An Empirical Investigation of Trade Liberalization and Trade Patterns in South Africa - Khumalo, Sibanisezwe Alwyn; Tsegaye, Asrat (Journal of Economics and Behavioral Studies, 2018)
The study made use of the gravity model to analyze the behavior of South Africa’s trade patterns at industry level. Using SIC 2-digit level data for the period 1996-2013 based on two sub-samples, 1996-2004 and 2005-2013, the study found that trade liberalization was not universally influential on trade patterns. Some industries did not exhibit significant behavior changes as a result of tariff liberalization. The results show that Agriculture, mining ores, crude oil, machinery and transport are the only industries from the selected sample of nine that are significantly influenced by trade liberalization policy. Furthermore, empirical results indicate that trade liberalization hinders extensive margins and does not encourage intensive margins.